A correlational study on the Relationship school culture and students’ moral development at secondary school level - Dr. Alamzeb; Mr. Ali Zeb Khan (International Research Journal of Education and Innovation, 2020)
School culture is an important component of students’ training and education. It informally influences the overall personality of students- including moral aspect of students. This study investigated the relationship between school culture and moral development of students from the perspectives of Kohlberg moral development theory. Students’ moral aspect was measured through a self-developed questionnaire taking into consideration the third stage of Kohlberg Moral development theory (12-17 years) which was correlated to the prevailing school culture at secondary school level. Similarly, school culture was delimited to school rule regulations, student teacher relationship, school climate and leadership which were investigated through the developed questionnaire. The data were collected from teachers and their students of government secondary schools and were analyzed through descriptive and inferential statistics. The results reflected that students have developed moral aspects of students which have close positive relationship with school culture. Based on the results it was recommended that school culture at school level may be made more balanced and according to the moral development of students.